RELATIONSHIP BETWEEN TOBACCO DEPENDENCE AND SCHIZOPHRENIA - Wayan Widhidewi (E-Jurnal Medika Udayana, 2014)
Tobacco dependence in schizophrenia patients is a problem that got more concern, withfew treatment options. Peoples with schizophrenia have a prevalence rate of cigarettesmoking two until four times higher than the general population. Consequently, patientsalso have a lower smoking quit rate than the general population. Tobacco dependence inthis population may complicate symptoms and also has adverse physiological effects onpatients. Besides that, patients with schizophrenia tend to smoke more heavily thansmokers in general population. This can increased smoking-related morbidity andmortality and impose a significant financial burden on patients. Recent studiesdemonstrated that patients with schizophrenia smoke before the onset of the illness andalso start smoking earlier than the average population. Patients become psychotic earlierthan patients who do not smoke, and require higher dose of anti-psychotic medications.